6y+2=-2

Simple and best practice solution for 6y+2=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y+2=-2 equation:


Simplifying
6y + 2 = -2

Reorder the terms:
2 + 6y = -2

Solving
2 + 6y = -2

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 6y = -2 + -2

Combine like terms: 2 + -2 = 0
0 + 6y = -2 + -2
6y = -2 + -2

Combine like terms: -2 + -2 = -4
6y = -4

Divide each side by '6'.
y = -0.6666666667

Simplifying
y = -0.6666666667

See similar equations:

| (m^2)*x+1=m*x+m | | 5y-8=-38 | | Graphx=-1+-0.3333 | | 12X-3X+516=5+5X+15 | | 25=y-7 | | 8y-3=2(2y+8) | | 86x-13=5 | | 8x-5(x-2)=x+24 | | -7u-1/3=1/2u-5/4 | | 3y+3(8+4g)=1-g | | 8x^2+15x+c=0 | | 34+2x=42 | | -4/5=-1/2u-4/3 | | -18+20x=-9 | | 2(x-8)=3(x-5) | | 6/5-4y=-18 | | 12x+4=7x-26 | | 58000+1.20x=15x | | .4(4x+11)=3(3-2x)+3 | | 1800+.01x=.06x | | -6(4x-9)+4=-24x+58 | | y+5.5=0.5(y+3) | | 6(x+2)-5=15-2x-8+8x | | -2/3x-3/2=-9/5 | | 1.7(4-x)=-.07(7-x) | | -2+4(x-4)=13x+3-9x | | 4(p-5)-3(2p+7)=1.5(2p-11) | | 3x+3=2(6x-2)+7 | | 4x-13=2x+4 | | -13x-18=1 | | (x+2.9)-(0.3x+4)=9 | | x+10=15-8 |

Equations solver categories